1998
DOI: 10.1111/j.1741-4520.1998.tb00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Restrained Fetal Movement on the Development of the Rat Hip Joint

Abstract: The effect of fetal movement on the development of the hip joint was examined by restraining the leg movement using exo utero operation in rat fetuses. At embryonic day (E) 16.5, when the hip joint cavity starts to form, one side of the hind limb was sutured onto the embryonic membrane. After exo utero development to E18.5, the hip joint of the operated side was compared morphologically with those of the unoperated side, sham‐operated and unoperated in utero controls. The largest diameter of the femoral head (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 23 publications
5
14
1
Order By: Relevance
“…The significance of fetal joint movement in normal joint development remains unknown. Kihara et al . (1998) examined the effect of restraining fetal hip movement on joint development by binding the hindlimb to the embryonic membrane with a 9–0 thread in E16.5 rat fetuses.…”
Section: Methodsmentioning
confidence: 99%
“…The significance of fetal joint movement in normal joint development remains unknown. Kihara et al . (1998) examined the effect of restraining fetal hip movement on joint development by binding the hindlimb to the embryonic membrane with a 9–0 thread in E16.5 rat fetuses.…”
Section: Methodsmentioning
confidence: 99%
“…The animals used were the same as above. We performed the ex0 utero operation at E16.5 as in the previous study (Kihara et al, 1998). At E16.5, pregnant rats were anesthetized with 50 m a g body weight pentobarbital for the fetal operation.…”
Section: Fetal Operation and Exo Utero Developmentmentioning
confidence: 99%
“…Immobilization of the hip joint in postnatal rats for the dislocation of the hip joint induced progressive acetabular dysplasia and anatomical abnormalities of the head and neck of the femur during the postnatal period (Sijbrandji, 1965). We previously studied the effects of fetal movement of the hind limb on the formation of the hip joint in rats, and reported that the fetal hind limb movement influenced the development of the femoral head (FH) and acetabulum (Kihara et al, 1998). We tied the hind limb on one side onto the embryonic membrane to restrict the range of motion at the hip joint at embryonic day (E) 16.5 using a technique of ex0 utero development (Muneoka et al, 1986;Hatta et al, 1994aHatta et al, , 1994bNaruse el al., 1996;Sekimoto et al, 1997;Zhang et al, 1998, Hatta et al, 2002, Matsumoto et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental system allows researchers to manipulate or operate on mid-to-late-gestation live embryos of mice or rats and keep them alive in situ until the analysis of their effects at a desired time point either pre-or postnatally. For example, we can examine the effects of injecting bioactive molecules or cells into targeted parts of a live embryo (Hatta et al 1994;Zhang et al 1998;Hatta et al 2002), transferring DNA into cells in a limited area (Takiguchi-Hayashi et al 2004), destroying specific embryonic regions (Naruse & Kameyama 1990;Naruse & Keino 1993;Naruse et al 1996), or performing fetal surgery (Kihara et al 1998;Habib et al 2005). In principle, the exo utero system enables us to make a time-and region-specific intervention into developmental phenomena simply by allowing us to choose the desired time and region for manipulation.…”
Section: Introductionmentioning
confidence: 99%